Genome-wide identification and functional characterization of the CP12 gene family in cotton reveals its critical role in heat stress response - Li, Chao; Li, Shuguang; Xu, Juan; Han, Ziling; Li, Wenlong; Zhao, Yanhai; Wang, Yanqin (Frontiers in Plant Science, 2025)
IntroductionCalvin Cycle Protein 12 (CP12) is a key regulator of the Calvin-Benson-Bassham (CBB) cycle that mediates CO₂ assimilation through dark/light modulation. Beyond its canonical role, emerging evidence indicates that CP12 may also function as a molecular chaperone and participate in plant stress responses. However, its gene family characteristics and roles under heat stress remain unclear in cotton.MethodsWe performed a genome-wide identification and characterization of the CP12 gene family in four cotton species (Gossypium hirsutum, G. barbadense, G. arboreum, and G. raimondii). Phylogenetic classification, conserved motif analysis, gene structure, synteny, and promoter cis-element analyses were conducted. Transcriptome datasets from flowers, leaves, and buds under heat stress were analyzed to determine expression patterns, and these were further correlated with physiological indicators.ResultsA total of 11, 10, 5, and 4 CP12 genes were identified in G. hirsutum, G. barbadense, G. arboreum, and G. raimondii, respectively. Phylogenetic analysis grouped them into three clades (I–III), supported by conserved motif and structural features. Synteny analysis indicated that whole-genome and segmental duplications were the primary drivers of expansion. Promoter analysis revealed enrichment of stress-responsive elements. Expression profiling showed clade-specific divergence: Clade I genes were strongly induced by heat stress, with Ghir_CP12_10 displaying ~10-fold upregulation in flowers, while Clade II genes were generally downregulated. These expression trends were associated with physiological changes, including reduced net photosynthetic rate and elevated malondialdehyde, catalase, and peroxidase levels.DiscussionOur findings demonstrate that the cotton CP12 gene family has undergone functional divergence. Clade I members act as positive regulators of thermotolerance, potentially stabilizing photosynthetic complexes and protecting enzymes from oxidative damage under heat stress. This study provides new insights into the evolution and function of CP12 genes and establishes a foundation for future functional validation and breeding of heat-tolerant cotton varieties.